มุมมองนักวิชาการในมหาวิทยาลัยราชภัฏรำไพพรรณี ต่อการเรียนการสอนการสื่อสารการตลาดแบบบูรณาการ - เส้งมณีย์, สมพงษ์ (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2019)
The purpose of this research is study the views of scholars in Rambhai Barni Rajabhat University towards teaching and learning Integrated Marketing Communication. To be a guideline for future teaching and learning development. By using qualitative research methodology. In-depth interviews with 4 related scholars and use the questions of Kerr and Kelly (2017). The research found that. 1. Course content, the content that scholars look at in the past, present and in the future, talking about various tool. Learning process about Integrated marketing communication. Various marketing communication tools will help each other. Using contextual tools can make the tool fully functional. 2. Scholars have commented that when technology comes IMC needs to be modified to match with the present. But should not leave traditional marketing communications. Scholars have given importance to consumers. The consumer behavior has changed. There are more options online. If conducting studies, it will enable the use of integrated marketing communication tools successfully. 3. Integrated teaching and learning process for marketing communication. Scholars think, providing students with self-learning will benefit children. The teaching and learning activities that focus on learners are important. The instructor should have a student education that is like a target group in order to be able to communicate directly, making students understand more.